When I grow up - Yankovic, Al, 1959-; Hargis, Wes (New York : Harper, 2011)
An exuberant eight-year-old details for his teacher and classmates the astonishing variety of inventive careers he is thinking of pursuing when he grows up.
Keywords: Stories in rhyme; Occupations -- Fiction; Show-and-tell presentations -- Fiction; Schools -- Fiction; Humorous stories